2021
DOI: 10.1007/s11356-021-17582-4
|View full text |Cite
|
Sign up to set email alerts
|

Income inequality, ecological footprint, and carbon dioxide emissions in Asian developing economies: what effects what and how?

Abstract: The reduction of income inequality and environmental vulnerability are two most important factors, through which we can achieve the target of Sustainable Development Goals (SDGs). The past papers have investigated the nexus between income inequality and carbon emissions, however, the relationship between income inequality and carbon emissions along with ecological footprint needs to be considered.To this end, the objective of current study is to reveals the causal association between income inequality and envi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 77 publications
1
15
0
Order By: Relevance
“…In addition, by ignoring CSD in panel data may lead to bias stationarity, co-integration, size misrepresentation, and as well as spurious regression results (Grossman and Krueger, 1995;Khan et al, 2021b). To this end, the current study uses Friedman (1937) and Pesaran (2004) test to identify the CSD between the units.…”
Section: Estimations Strategy and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, by ignoring CSD in panel data may lead to bias stationarity, co-integration, size misrepresentation, and as well as spurious regression results (Grossman and Krueger, 1995;Khan et al, 2021b). To this end, the current study uses Friedman (1937) and Pesaran (2004) test to identify the CSD between the units.…”
Section: Estimations Strategy and Resultsmentioning
confidence: 99%
“…From the one aspect of energy-poverty, the gradual increase in access to clean fuel and technology for heating and cooking can signi cantly control the rising trend in Co2e; but, the imperfect energy supply structure, lack of investment in energy sector, and poor energy management so far lead to an increase in Co2e (Zhao et al, 2021a). In past few years, many developing countries in Asia such as China has achieved tremendous economic growth (Khan et al, 2021b). Nevertheless, due to regional energy-inequality and differences in economic performance, extreme energy-poverty exists in developing countries, particularly in Asia (Apergis et al, 2021;Zhao et al, 2021b).…”
Section: Estimations Strategy and Resultsmentioning
confidence: 99%
“…Findings indicated a positive relationship among CO 2 , ECO, and GINI. Khan et al (2022) extended the model for the same period and same country group by adding the poverty variable to Khan and Yahong (2021). They found that GINI and poverty increase ED.…”
Section: Literature Reviewmentioning
confidence: 98%
“…The findings showed that GINI positively affects ECO. Khan and Yahong (2021), using the Driscoll and Kray methodology, researched the impact of GINI on CO 2 and ECO in 18 Asian countries. Findings indicated a positive relationship among CO 2 , ECO, and GINI.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One can argue that potential differences exist between developed and developing countries. However, such disagreement would be simplified as the empirical evidence indicates significant differences, even within developed and developing sectors (Tamazian et al 2009, Tamazian and Bhaskara Rao 2010, Jalil and Feridun 2011, Chang 2014, Abbasi and Riaz 2016, Javid and Sharif 2016, Solarin et al 2017, Shahbaz et al 2018, Zakaria and Bibi 2019, Ahmed et al 2021, Khan and Yahong 2022. At the same time, it is necessary to carry out a detailed analysis, specific to the economy concerned, before drawing a conclusion on ecological consequences of economic growth.…”
Section: Introductionmentioning
confidence: 99%